Mechanisms of bacterial membrane permeabilization by crotalicidin Ctn and its fragment Ctn 15–34, antimicrobial peptides from rattlesnake venom - Peinado, Clara Pérez (2019)
© 2018 by The American Society for Biochemistry and Molecular Biology, Inc.